Tuberculous Otomastoiditis: a case report. - Subha, Sethu Thakachy; Puraviappan, Periyannan; Abd Majid, Nasir; Prepageran, Narayanan (Poracom Academic Publishers, 2008)
Tuberculosis is on the rise in the recent years. Commonest presentation is tuberculosis of the lungs. Tuberculosis of the middle ear cleft is relatively uncommon and often missed by clinicians. A case of tuberculous otomastoiditis with intracranial complication is presented. This case report is to emphasize the fact that high index of clinical suspicion is necessary for the early diagnosis and treatment of this entity which can cause fatal consequences.